(3OQGSI ehGbY GdJQGK GdeYeGQj GdESdGej HGdeOjfI GdbOjeI HfGHdS aj adSWjf (B:s (3OQGSI CKQjI eYeGQjI ebGQfI (B/s - (3,TjeGA SjO TGcQs; (3YHO GdYRjR UdGM SGdes (2024)
(3JJfGhd GdQSGdI OQGSI eOjfI fGHdS EMOi Cge eOf adSWjf JGQjkNG hEMOi Cge eOf GdVaI GdZQHjI, hPdc HJMdjd ebheGJgG GdJGQjNjI hechfGJgG GdCKQjI hGdJQGKjI, ddhbha Ydi CgejJgG cfehPL deOf GdJQGK GdYeQGfj HeG JTJed Ydjg ef BKGQ eNJdaI eJYOOI heJfhYI, heYQaI ehbYgG GdLZQGaj hfTCJgG GdJGQjNjI hCTgQ GdCMOGK GdJj eQJ Ydi GdeOjfI efP hbJ EfTGFgG, hQcRJ GdQSGdI GdMOjK Yf GdHdOI GdbOjeI HGYJHGQgG GdehbY GdCbOe hGdCcKQ CUGdI Vef eMjW GdeOjfI ccd, EP JfbSe Edi YOI MGQGJ HOGNd cd efgG ebheGJ GdeYjTI hGdMjGI GdGbJUGOjI hGdGLJeGYjI, hbO dYHJ GdeHGfj GdCKQjI OhkQG cHjkQG aj gPg GdCfTWI, EP fLO GdYeGFQ GdOjfjI ef eSGLO heOGQS hCVQMI hRhGjG, hYeGFQ eOfjI ef NGfGJ hCShGb hCSHdI hMeGeGJ hbUhQ, hZjQ Pdc eeG cGf SHkHG aj MjGI GdeOjfI, eY GdETGQI Edi GdeOjfI HGYJHGQgG ehbkYG JQGKkjG, aJfGhdJ GdOQGSI eaGgje GdJQGK heMGhdI ESbGWgG Ydi GdHdOI GdbOjeI HfGHdS, hLGAJ GdOQGSI Ydi GdfMh GdJGdj(B:(3ebOeI(B: (3JJfGhd CgejI GdehVhY hCSHGH GNJjGQg hCge GdOQGSGJ GdSGHbI(B. (3JegjO(B: (3jNU GdEWGQ GdLZQGaj hGdJGQjNj ddHdOI GdbOjeI HfGHdS, hbO Je JbSje GdOQGSI HYO GdJegjO Edi CQHYI aUhd(B:(3hjJfGhd GdaUd GdChd GdYeGFQ GdCKQjI GdOjfjI GdHGbjI HGdHdOI GdbOjeI HfGHdS,(B:(3hjJfGhd GdaUd GdKGfj GdYeGFQ GdCKQjI aj GdYeGFQ GdeOjfI PGJ GdCZQGV GdJj Jbhe HgG GdMjGI aj GdeOjfI, CeG GdaUd GdKGdK aLGA HYfhGf NUGFU hebheGJ GdHdOI GdJQGKjI GdbOjeI HfGHdS, hJe ajg OQGSI eOjfI fGHdS HhUagG ehbkYG Ch eOjfI ddehGbY GdJQGKjI(B. (3CeG GdaUd GdQGHY ef GdOQGSI ajJfGhd GdJhXja GdCKQj hGSJOGeI GdehGbY GdJQGKjI OGNd GdHdOI GdbOjeI HfGHdS, hJCJj GdNGJeI HYO Pdc dJJfGhd Cge fJGFL GdOQGSI, jdjgG GdeUGOQ hGdeQGLY Ke cJGdhL GdNQGFW hGdCTcGd hGdUhQ(B.s
The author of a study of the city of Nablus, one of the most important cities in Palestine historically and one of the most important cities in the West Bank, by analyzing its historical components and its influential and heritage components, to identify the most important of them as a model for urban heritage cities, including their influence from very different influences, and knows its geographical location, its historical origins, and the most famous events that began since the time of the city$1 (Bs establishment. The modern thesis focused on the old city only, only the oldest, originality within the surroundings. The city as a whole, as it is divided into several neighborhoods, each of which contains the elements of living, economic and social life, and the archaeological buildings played a major role in these activities, as we find religious buildings such as mosques, schools, shrines and corners, and civil buildings such as khans, markets, avenues, baths, palaces, and other things that were the reason for the life of the city, with reference to the city as a heritage site, so the study dealt with the concepts of heritage and the attempt to project them onto the old city of Nablus. The study was as follows: Introduction: It discusses the importance of the topic, the reasons for choosing it, and the most important previous studies. Introduction: It concerns the geographical and historical framework of the Old City of Nablus. After the introduction, the study was divided into four chapters: The first chapter deals with the remaining religious archaeological buildings in the Old City of Nablus. The second chapter deals with the archaeological buildings in the city buildings that serve the purposes of life in the city. The third chapter was entitled Characteristics and components of the old heritage town in Nablus, in which the city of Nablus was studied as a site or city for heritage sites. The fourth chapter of the study deals with archaeological employment and the sustainability of heritage sites within the Old City of Nablus, and the conclusion comes after that to address the most important results of the study, followed by sources and references, then a catalog of maps, figures, and pictures.s
(3CWQhMI (B((3eGLSJjQ(B)-(3LGeYI GdbGgQI, (B2024. s
(3HHdjhLQGajG(B: (3UaMGJ (B250-267.s
(3UOQ CjkVG cbQU eOeL(B.s
(3GdfU HGdYQHjI hGdedNU HGddZI GdEfLdjRjI hGdYQHjI(B.s
Keywords: (3GdYeGQI GdGSdGejIs -- (3adSWjfs; a